Analisis Kreativitas Peserta Didik Kelas 4 SD Dalam Pembelajaran Menggambar Perspektif - Eva Lailatul Manjilah; Zuhrotul Isnaini; Intan Kumala Sari; Wanda Dwi Nastiti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze the creativity of 4th grade elementary school students in learning perspective drawing. This type of research is descriptive qualitative. This research wasconducted at SD 2 Dersalam, 10 November 2023. The subjects used as respondents for this research were grade 4 at SD 2 Dersalam. The data collection techniques used in this research are observation and documentation. The data analysis used is descriptive qualitative. The analysis results obtained from student drawing documentation meet the creativity criteria of high creativity, medium creativity, low creativity and show that drawing using perspective techniques is able to hone students’ creativity, because they are able to be creative according to their own creativity.